KINEMATICS ANALYSIS OF SUSPENSION THROWING IN HANDBALL (Fiep Bulletin - online, 2014)
The focus of this study is the suspension pitch in handball. To make an analysis of this pitch, a kinematic movement study was made, in which were examined variables as; the phase time of the pitch, max angle flexion of the knee, height and exit velocity of the ball, and the average behavior of the shoulder elbow during the time of the aerial phase of the pitch. A two-dimensional kinematic videography system was used to produce the analysis, and for the digitalized analysis of the data was used the simi twinner pro system Pro. The purpose was to analyze the kinematics of the suspension throwing of the team, through space-time variables in the performance of the female athletes about the success of the shot. The data collection was performed on a normal day of training, where athletes performed a warm up for the images of the pitches that were to be done in the continuation. After this, the data were analyzed and significant results were discovered, turns out the team demonstrated a good technical level when compared with the study of the Brazilian national team of handball the data were close or higher as in the time variable phase of suspension shot that the team reached 0.32 ± 0.06s and compare with other author which resulted in 0.34 ± 0.09s or the ball output speed variable that the analyzed team had was of 21.78 ± 4,11m/s and the national team reached 19.34 ± 1.32 m/s. The result is that the team presented a good technical level in the variables, the advantage of the pitches used was of 75%.
Keywords: Kinematic of the movement; Handball; Suspension Throwing